2020
DOI: 10.1039/d0ta07543d
|View full text |Cite
|
Sign up to set email alerts
|

Highly stretchable supramolecular conductive self-healable gels for injectable adhesive and flexible sensor applications

Abstract: The synergistic supramolecular networks of conductive self-healable gels (CSGs) containing polythioctic acid (PTA), Fe3+ ion, pyromellitic acid (PA), and interpenetrating polyaniline (PANI) are synthesized and developed in this study. These...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 48 publications
1
47
1
Order By: Relevance
“…ROP) and then crosslinking the material via metal coordination/complexation of the carboxylate moiety. [40][41][42][43][44][45][46] Other studies have also modified the carboxylic acid of lipoic acid with dopamine 47 or N-hydroxy succinimide 48 to produce self-healing supramolecular adhesives. Additionally, dynamic cyclic disulfides have also featured in degradable nanoparticles 49,50 and adaptable hydrogels [51][52][53][54] , although in the gel examples the disulfide features as a reactive polymer a.…”
Section: Introductionmentioning
confidence: 99%
“…ROP) and then crosslinking the material via metal coordination/complexation of the carboxylate moiety. [40][41][42][43][44][45][46] Other studies have also modified the carboxylic acid of lipoic acid with dopamine 47 or N-hydroxy succinimide 48 to produce self-healing supramolecular adhesives. Additionally, dynamic cyclic disulfides have also featured in degradable nanoparticles 49,50 and adaptable hydrogels [51][52][53][54] , although in the gel examples the disulfide features as a reactive polymer a.…”
Section: Introductionmentioning
confidence: 99%
“…The HV12 ionogel exhibited the maximum shear stress value of 120 kPa at a polymer concentration of 40 wt%, which is comparable to or higher than those of other adhesive materials used in skin sensor applications (Table S4, Supporting Information). [ 34–37,69–77 ] The trend in the shear stress with polymer concentration can be explained by the amount of functional groups and the chain mobility of the polymer network. At low polymer concentrations, addition of HV12 polymer increases the amount of functional groups that induce noncovalent interactions with target substrates.…”
Section: Resultsmentioning
confidence: 99%
“…For wearable and stretchable sensors, the ionogels must securely adhere to the surface of the target object for reliable detection of movement. [ 34–37 ] However, typical sensing materials reported in the literature are not adhesive and require adhesive tapes or bandages to fix the device to the skin, which decreases the sensitivity of the device. [ 37–39 ] The continuous use of non‐adhesive wearable sensors may even cause devices or appendages to peel off the surface.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, its tunability and facile fabrication process with low cost make this supramolecular pressure sensor potentially useful for real-time human health monitoring using wearable electronics. There have also been reports on supramolecular, stretchable pressure sensors such as the conductive self-healable gels (CSGs) by Khan and co-workers ( Khan et al, 2020 ). This study reported a supramolecular gel, containing polythioctic acid (PTA), pyromellitic acid (PA), Fe 3+ and a polyaniline (PANI) network, that is highly sensitive (2.8 kPa −1 ), stretchable (>5,000%), and has good strain sensitivity (gauge factor of 11).…”
Section: Other Transduction Mechanisms For Supramolecular Biosensorsmentioning
confidence: 99%